ADULT LEARNER’S CHARACTERISTICS - Pazin Filho, Antonio (Medicina (Ribeirao Preto), 2007)
The characteristics of the adult learner are discussed: background and refractoriness to the acquisition of new knowledge unless it can be integrated; the demand of respect to this background; the need of motivation; the need to share experiences; the need of immediate implementation of the new concepts acquired; the fear to err; the need of feed back. The lack of knowledge of these characteristics can threaten the lecture in several ways that are illustrated along with the techniques to deal with these problems.